Don’t tell me, train me: Employee training, as the most significant contributing factor to employee performance in north of Malaysia’s tourism industry - Diyana, Kamarudin; Faiz, Azizul; Haziman, Zakaria; Tan, Li Mi (Science Research Society, 2021)
Globally, the tourism industry contributed nine percent of the world’s Gross Domestic Product (GDP). The tourism industry has many and various competitors, regardless of small or large industry players. To ensure this industry resilience and remain competitive, employees have become an essential resource in helping companies stay competitively ahead. This study delves into the methods that can help increase the employees' performance within the tourism industry. Four factors were addressed in this study, forming a causal model with a mediator. This study was administered using purposive sampling on 140 employees from 20 tourism-based companies in northern Malaysia by distributing questionnaires. Items were quantitatively analyzed using SPSS for demographic analysis and Smart-PLS 3.0 to assess the formative measurement models' PLS-SEM results. PLSSEM analysis indicated that there is a significant relationship between the variables. Training and effective communication were the most effective contributing factors towards marketing competencies towards employee performance with a p-value > 0.05. The outcome of this research suggests that companies should construct innovative and novel ways to measure, train and manage of staff performance, which includes the way they communicate with their employees on the feedback process.